Automatic Test Case Generation from UML Activity Diagram Using Activity Path - Almulham, Yasir Dawood Salman (2010)
The most important part of the testing attempt is the test case generation. As a modeling language, Unified Modeling Language (UML) is the most generally used to describe design specifications and analysis by both academic and industry. Therefore, UML becomes the sources of Test Case Generation. Test cases are usually generated from the requirement, and UML activity diagram illustrates the sequential control flows of activities what make it possible to generate test cases for activity diagrams. This research proposes an approach to automatically generate test cases directly from UML activity diagram using activity graph. Therefore, this research will create an algorithm and implement it on a prototype using the UML activity diagram as an input to generate the test cases. The result of all these test cases will be compared to the result that has been generated manually to evaluate the usability and reliability of the proposed algorithm.